2021
DOI: 10.21203/rs.3.rs-139944/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resveratrol Protects Human Nucleus Pulposus Cells from Degeneration by Blocking IL-6/JAK/STAT3 Pathway

Abstract: Background: Nucleus pulposus cells’ (NPCs’) degeneration is mainly responsible for the intervertebral disc degeneration (IDD), which is closely related to inflammatory response. Among the major proinflammatory factors that are related to NPCs’ degeneration, interleukin-6 (IL-6) and its downstream JAK/STAT3 pathway have received recent attention. The goal of our study is to figure out whether or how resveratrol (RSV) can protect NPCs from degeneration by affecting IL6/JAK/STAT3 pathway. Methods: Different conce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…IL-6 could aggregate in ammatory cells, regulate the overexpression of matrix metallolytic enzymes, promote the degeneration of extracellular matrix, and enhance IVDD (41). It was found that resveratrol improved NPCs growth and degeneration of extracellular matrix by IL-6/JAK/STAT3 pathway (42). The study have con rmed that IL-1β and TNF-α are highly expressed in IVDD tissues compared with normal intervertebral disc tissues (43).…”
Section: Discussionmentioning
confidence: 74%
“…IL-6 could aggregate in ammatory cells, regulate the overexpression of matrix metallolytic enzymes, promote the degeneration of extracellular matrix, and enhance IVDD (41). It was found that resveratrol improved NPCs growth and degeneration of extracellular matrix by IL-6/JAK/STAT3 pathway (42). The study have con rmed that IL-1β and TNF-α are highly expressed in IVDD tissues compared with normal intervertebral disc tissues (43).…”
Section: Discussionmentioning
confidence: 74%
“…It has been reported that once STAT3 is activated via phosphorylation, STAT3 forms dimers to interact with the reciprocal phosphotyrosine‐SH2 domain, which quickly translocate to the nucleus, where STAT3 binds to DNA and induces the expression of target genes 15,20 . Hence, STAT3 distribution in the nuclear and cytosolic fractions was analysed.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that once STAT3 is activated via phosphorylation, STAT3 forms dimers to interact with the reciprocal phosphotyrosine-SH2 domain, which quickly translocate to the nucleus, where STAT3 binds to DNA and induces the expression of target genes. 15,20 Hence, STAT3 distribution in the nuclear and cytosolic fractions was analysed. As shown in Figure 3A TAC-induced mice displayed a significant increase in heart mass, while the ratios of heart weight to body weight (HW/BW) and heart weight to tibial length (HW/TL) were reduced following treatment with PM (Table 1).…”
Section: Pm Inhibited Nuclear Translocation Of Stat3 In H9c2 Cellsmentioning
confidence: 99%
See 2 more Smart Citations